Penentuan Jenis Fluida Reservoar Di Lapangan M, Blok N, Sumatera Selatan - Nugroho Marsiyanto (Jurnal Bhara Petro Energi, 2024)
Reservoir  fluid  type  in  oil  or  gas  field  must  be  determined  very  early  in  the  life  of  reservoir because  it  is  as  critical factor  in  many  of  decisions  made  about  producing  strategy of  the fluid from the reservoir. It also influence in the depletion reservoirs strategy. Reservoir fluid type can be confirmed only by observing a representative fluid sample in the laboratory testing. However, rules  of  thumb  based  on  production  data  such  as  initial  producing  GOR,  stock  tank  liquid gravity, and stock tank liquid color usually will indicate reservoir fluid type of those reservoirs. M field was discovered in December 1989 with the drilling of M-1 well.  Subsequently, in July 1991, the M-2 well was drilled.  In November 1997, an appraisal well, M-3, was drilled. Based on total production testing at M field indicated that the potential deliverability is 30 MMSCFD and M field have  being  produced  since  March  2002  up  to  date  from  those  three  wells.    Objective  of  this paper is to determine fluid type in this M field. Based on the laboratory testing data from those 3 wells, the heptane plus concentration of M1 well is 0.47 % mole, the heptane plus concentration of M2 well is 0.67 % mole, and the heptane plus concentration of M3-well is 0.64 % mole. The Initial  Gas  Oil  Ratio  of  M  field  refer  to  well  testing  is  ranging  from  from  75,000  scf/STB  to 554,545  scf/STB  which  is  high  GOR  producing.    Based  on  those  2  methods  to  determine reservoir fluid types, the laboratory testing and rules of thumb on intial production data, the fluid type of M field is categorized as A Dry Gas. This fluid determination is giving the advantages of strategic field drainage optimally and economically to the field.